TELAAH KRITIS TERHADAP PERLINDUNGAN FREEDOM OF SPEECH DALAM HONGKONG SECURITY LAW DITINJAU BERDASARKAN DEKLARASI BERSAMA TIONGKOK – INGGRIS 1984 (SINO-BRITISH JOINT DECLARATION 1984) - Madeleine Lie; Ida Kurnia (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2022)
The Sino-British Joint Declaration was a declaration that was signed by Great Britain and China in 1984 in other to discusses about Hongkong which was under British control at that time where British gave Hongkong to China as the part of 99 year lease, but it ended up in disaster after the Hongkong's 2020 National Security Law.The type of research that the author uses is normative where this research refers to international regulations that apply in international relations, court decisions, and norms that apply in international relations.Based on the studies that have been carried out and based on expert opinions and theories that have been put forward, it can be concluded that China violated the contents of the Sino-British Joint Declaration which protects the principle of Freedom of Speech in Hongkong with the ratification of the Hongkong National Security Law.Based on the conclusions above, the authors provide the following suggestions, the Chinese government must carry out International Responsibility by revising the Hong Kong National Security Law both in substance (to avoid rubber articles such as Article 29 point 5) and the process of making the law to follow the law-making procedures in force in Hong Kong.